2003
DOI: 10.1126/science.1080190
|View full text |Cite
|
Sign up to set email alerts
|

Positional Cloning of the Human Quantitative Trait Locus Underlying Taste Sensitivity to Phenylthiocarbamide

Abstract: The ability to taste the substance phenylthiocarbamide (PTC) has been widely used for genetic and anthropological studies, but genetic studies have produced conflicting results and demonstrated complex inheritance for this trait. We have identified a small region on chromosome 7q that shows strong linkage disequilibrium between single-nucleotide polymorphism (SNP) markers and PTC taste sensitivity in unrelated subjects. This region contains a single gene that encodes a member of the TAS2R bitter taste receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
714
1
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 800 publications
(759 citation statements)
references
References 30 publications
33
714
1
11
Order By: Relevance
“…18 It was soon determined that the trait was heritable (i.e., transmitted in families), 40 and 70 years later the responsible gene and allele were identified. 41 The gene, called TAS2R38, is a member of the bitter taste receptor family TAS2R. Three alleles in TAS2R38 account for the bitter-blindness to PTC—they combine to form a haplotype that leads to reduced ability to perceive PTC (and its chemical relative propylthiouracil, one of the commonly studiedbitters listed above).…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
See 1 more Smart Citation
“…18 It was soon determined that the trait was heritable (i.e., transmitted in families), 40 and 70 years later the responsible gene and allele were identified. 41 The gene, called TAS2R38, is a member of the bitter taste receptor family TAS2R. Three alleles in TAS2R38 account for the bitter-blindness to PTC—they combine to form a haplotype that leads to reduced ability to perceive PTC (and its chemical relative propylthiouracil, one of the commonly studiedbitters listed above).…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…The differences among people in the ability to smell androstenone are at least partially determined by genes, 151,152 and an allele of an OR gene, OR7D4, contributes to this trait. 153 However, unlike alleles of the taste receptor gene TAS2R38, which account for almost 70% of the person-to-person variation in perception of bitter taste from PTC, 41 OR7D4 alleles account for only a small amount of variance in perception of androstenone. 153 Two other OR genes have been associated with individual variation in the sense of smell: OR11H7 with isovaleric acid (sweaty odor) 154 and OR2M7 with the smell of asparagus metabolites in urine.…”
Section: Smellmentioning
confidence: 99%
“…It was suggested that the derived allele may provide better protection against harmful cyanogenic plant foods and natural toxins (Soranzo et al 2005) . Another interesting case is the T2R38 gene, which is largely responsible for the human polymorphism in tasting phenylthiocarbamide (Kim et al 2003) . Balancing selection was suggested to maintain both taster and nontaster T2R38 alleles in human populations (Wooding et al 2004) , although a subsequent analysis found the evidence for balancing selection unconvincing (Wang et al 2004) .…”
Section: Adaptive Diversification Of Chemoreceptor Gene Repertoiresmentioning
confidence: 99%
“…Recent studies have raised the possibility that most genotype-phenotype association studies are based on rare gene disruptions arising during mammalian evolution (27,28). In fact, some taste receptors also seem to be affected by mutations during mammalian evolution (6,7,12,13,(29)(30)(31). For example, the hT2R43 W35 allele makes people most sensitive to the bitterness of the natural plant toxins, aloin and aristolochic acid, and an artificial sweetener, saccharin, compared with S35 allele (31).…”
Section: Introductionmentioning
confidence: 99%
“…7 between intact and pseudogene forms. Isolated cases of segregating mutations in taste receptors have been reported (6,7,12,13,(29)(30)(31)). …”
Section: Introductionmentioning
confidence: 99%